GLOBAL TRENDS IN HUMAN RESOURCE ACCOUNTING THROUGH BIBLIOMETRIC ANALYSIS ON SCOPUS DATABASE - Dermawan, Wildan Dwi (Media Riset Akuntansi, Auditing & Informasi, 2024)
This study aims to map the topic of human resource accounting using the Scopus database with a time span from 1972 to 2023. The keyword used "human resource accounting" obtained as many as 153 documents. The software used is R biblioshiny. The results show that the development of research is increasing from year to year even in 2019 experienced a significant increase. Accounting Organization and Society as the most relevant journal as well as the journal that has the highest impact on human resource accounting research. Meanwhile, Eric G. Flamholtz from the United States of America as the author who has the most influence on the development of research on human resource accounting. the topic of human resource accounting since 2010 and is discussed continuously until 2021 so that it has the most frequency compared to other topics. Another topic, namely human capital, is the latest topic that is currently developing and is a recommended research topic in the future.